Early outcomes assessment of tonsil cancer treatment by IMRT technique - Hoang, Nguyen Hoai An; Pham, Nhu Hiep; Phan, Canh Duy; Ho, Thi Thanh Phuong; Nguyen, Huu Minh Tuan; Nguyen, Van Cuong (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2016)
Introduction: In this study, the authors present the results in the application of IMRT technique for tonsil cancer at Hue Central Hospital. Materials and methods: Prospective study on 31 patients with tonsil cancer from March 2015 to May 2016 by IMRT technique. Mean age was 62.32 ± 14.31 years old (range: 40-92 years old), 80.6% were male. Results: The follow-up time was 3 months for surviving patients. The predominant T and N stage were T3 (90.3%), N1 (58.1%) and N2 (25,8%). Good and moderate histological differentiation of the tumors accounted for 81.7%. Complete response rates of the primary tumor and the nodal disease were 96.8% and 93.5%, respectively. Grade 3 mucositis occurred in 32.3% of patients. Xerostomia grade 2 was recorded in 67.7% of the patients. Conclusions: The results indicate that IMRT technique provides satisfactory results and should be applied in treatment of tonsil cancer.